2018
DOI: 10.21276/aimdr.2018.4.2.py1
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Addiction among Students of Medical University in South India: A Cross-Sectional Study

Abstract: Background: Smartphone has become an integral part of our daily living. The problem of smartphone addiction is growing across the world especially among students. Aim: This study was conducted to know the magnitude of smartphone addiction among students of the medical university. Methods: It is a questionnaire based cross section observational study conducted at Yenepoya University campus, Mangalore, Karnataka State, South India, from July 2017 to November 2017 involving 328 students from all constituent colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…India has the fastest growing mobile user base in the world with 90 mobile connections per 100 of the population [ 14 ]. All the respondents in our study owned mobiles (100%), which is in concordance to other studies conducted among Indian medical students [ 15 ]. 59.4% were at high risk of mobile addiction according to the SAS-SV scale.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…India has the fastest growing mobile user base in the world with 90 mobile connections per 100 of the population [ 14 ]. All the respondents in our study owned mobiles (100%), which is in concordance to other studies conducted among Indian medical students [ 15 ]. 59.4% were at high risk of mobile addiction according to the SAS-SV scale.…”
Section: Discussionsupporting
confidence: 90%
“…81.1% reported more than 4 hours/day of screen time. This is substantially higher than the 60% reported by Ammati et al and the 46% reported by Dasgupta et al in 2017, among medical students from West Bengal [ 15 , 19 ]. The ongoing COVID-19 pandemic, which has shifted teaching from lecture halls to online virtual classrooms, may be the cause for this discordance.…”
Section: Discussionmentioning
confidence: 55%
“…Regarding gender and SA association, the current study showed high addiction prevalence between both gender and showed highly significant association between gender and smartphone addiction which revealed that male students are more addict to smartphone than female students. Same results found by Hasan et al in 2018 in Kirkuk university among Nursing students; also, Alosaimi et al, 2016;Dixit et al, 2010;Alhazmi et al, 2018;Ammati et al, 2018;and Bisen and Deshpande, 2016 found that smartphone addiction was higher in male than females participants students. However, disagree to our current study findings, some studies reported that female has a higher prevalence of smartphone addiction than males (Demirci et al, 2014;De-Sola et al, 2016;Jain et al, 2019;Tavakolizadeh et al, 2014).…”
Section: Discussionsupporting
confidence: 51%
“…[ 24 ] in China and Ammati et al . [ 25 ] in South India. The reasons for higher smartphone addiction in Andaman and Nicobar Islands may include that Andaman and Nicobar Islands is a geographically secluded area from mainland India with limited avenues for other kinds of social interactions or recreational activities especially for students from mainland India.…”
Section: Discussionmentioning
confidence: 99%